Ecological Studies of Climate Factors and Pulmonary Tuberculosis Cases in Padang City 2020-2023 - Hamda Fadilah Habibul; Al Asyary; Roma Yuliana; Arinil Haq; Soraya Permata Sujana (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Tuberculosis (TB) is actually a disease that can be prevented and cured. In 2022, TB became the second leading cause of death in the world after Coronavirus (COVID-19), and caused twice as many deaths as HIV/AIDS. Several studies have stated that climate factors such as exposure to high temperatures, dry environments and exposure to ultraviolet light can influence the growth of Mycobacterium tuberculosis. Objective: This research aims to determine the distribution and correlation of climate factors with the number of pulmonary TB cases in Padang City in 2020-2023. Method: This research is an ecological study with the study population of Padang City. In this study the dependent variable is pulmonary TB cases and the independent variables are temperature, precipitation, and humidity. Pearson correlation is used to determine whether or not there is a relationship, the strength of the relationship, and the direction of the relationship between two normally distributed numerical variables. This research also describes descriptively the distribution of pulmonary TB cases in Padang City based on sub-districts using spatial analysis. Result: There is significant relationship in 2022 between temperature (p=0.010) and precipitation (p=0.019) with pulmonary TB cases in Padang City. However, there are no variables of climates related to pulmonary TB when analyzed cumulatively from 2020-2023. Based on the results of spatial analysis, it can be seen that Koto Tangah sub-district is consistently in the high category of pulmonary TB cases in 2020-2023. Conclusion: The research results found that temperature and precipitation in 2022 were significantly related with the incidence of pulmonary TB, while the humidity variable had no significant relationship with the incidence of pulmonary TB cases in Padang City. It is recommended to make climate factors such as one of the considerations in making policies related to the prevention of pulmonary TB.